Effects of uncomplicated carotid endarterectomy on cognitive function and brain perfusion in patients with unilateral asymptomatic severe stenosis of the internal carotid artery by comparison with unoperated patients. (2nd July 2016) - Kojima, Daigo; Ogasawara, Kuniaki; Kobayashi, Masakazu; Yoshida, Kenji; Kubo, Yoshitaka; Chida, Kohei; Oshida, Sotaro; Yoshida, Jun; Fujiwara, Shunro; Terasaki, Kazunori
Abstract : Objective: The purpose of the present exploratory study was to evaluate the effects of uncomplicated carotid endarterectomy (CEA) on cognitive function and brain perfusion in patients with unilateral asymptomatic severe stenosis of the internal carotid artery (ICA) by comparison with unoperated patients. Methods: Patients with age ≤75 years and unilateral asymptomatic severe stenosis (≥70%) of the cervical ICA underwent CEA with antiplatelet therapy (surgically treated group: 116 patients) or antiplatelet therapy alone or neither (medically treated group: 45 patients). For the surgically treated group, neuropsychological testing and brain perfusion measurement using single-photon emission computed tomography were performed within one month before surgery and one month after surgery. For the medically treated group, the same testing and measurement were performed twice at an interval of 1 to 2 months. Results: None of the operated patients developed new major ischemic events after surgery or intraoperative cerebral hyperperfusion. None of the patients in the medically treated group experienced neurological deficits including transient ischemic attacks during the study period. The incidence of patients with interval cognitive improvement was significantly greater in the surgically treated group (11 patients: 9%) than in the medically treated group (0%) ( p = 0.0352). The incidence of patients with interval brain perfusion improvement in the ipsilateral cerebral hemisphere was significantly greater in the surgically treated group (24 patients: 21%) than in the medically treated group (0%) ( p = 0.0003). Conclusions: Uncomplicated CEA may improve cognitive function and brain perfusion in patients with unilateral asymptomatic severe stenosis of the ICA when compared with unoperated patients.